(untitled) (Faridpur Medical College Journal, 2025)
Rheumatoid arthritis is a chronic, systemic, autoimmune inflammatory disorder affecting various tissues and organs like skin, blood vessels, heart, lungs, and muscles. Vasculitis is an important one of the extra-articular manifestations, leading to gradual thickening of intima-media and atherosclerotic arterial disease. This case control study was carried out to compare the intima-media thickening of both the common carotid and femoral artery between rheumatoid and non-rheumatoid arthritis subjects by high resolution B-mode ultrasonography as well as assessing plaque prevalence in the common carotid artery in Rheumatoid arthritis and morphologic evidence of sub-clinical atherosclerosis in RA patients. Total 40 adult patients with rheumatoid arthritis were taken as cases & 20 matched healthy people were taken as controls. Common Carotid artery intima-media thickness was greater in patients than in controls (mean ± SD 0.52 ±0.09 vs 0.37± 0.08mm, p<0.001). Similarly, the intima medias of both right and left femoral arteries of the Rheumatoid arthritis patients were considerably thicker than controls (0.67 ± 0.19 vs. 0.39±0.04, p< 0.001 and 0.62±0.17 vs.0.39 ±0.04, p<0.001). Six cases (15%) had calcification at femoral arteries. None of the controls exhibited plaque or calcification in any parts of common carotid or femoral arteries. The outcomes of the present study specified that Rheumatoid arthritis patients had increased thickness of intima media of the carotid and femoral artery which were the manifestations of atherosclerosis. Rheumatoid arthritis was usually associated with increased arterial wall thickness with or without plaque or calcification. Faridpur Med. Coll. J. 2025;20(1): 46-50